Perceived Risk of COVID-19 and Employee Decision-Making: How Psychological Distress during the Pandemic Increases Negative Performance Outcomes among Healthcare Workers - Moyo, Ngqabutho; Bhappu, Anita D; Bhebhe, Moment; Ncube, Farai (MDPI, 2022)
In this research, we examined how COVID-19 impacts employee decision-making and performance, knowing that this virus has negatively affected public health, crippled economies, and transformed social and business environments across the globe. To quantitatively test our specific hypotheses regarding the effects of employees' perceived risk of COVID-19 and psychological distress on negative performance outcomes, we surveyed 443 healthcare workers who were employed by a group of private hospitals in Zimbabwe. These essential workers were delivering day-to-day frontline services with high exposure to COVID-19 during the pandemic. We find that employees' perceived risk of COVID-19 increases their disengagement, turnover intention, burnout, and low morale at a p < 0.05 significance level. These latter relationships are mediated by employees' psychological distress at a p < 0.05 significance level. Our findings shed light on how the COVID-19 pandemic is affecting the cognitions and behaviors of the frontline workers who are vulnerable to this contagious disease. Turnover intentions are amplified among healthcare employees, due to their perceived risk of COVID-19 and the resulting psychological distress. Similarly, burnout becomes predominant as these workers worry about contracting the coronavirus due to the poor working conditions they face. As such, our research confirms that the pandemic has intensified the precariousness of work and challenge of managing employee performance, especially for frontline healthcare workers.